The Effect of Cold Compresses on the Comfort of the Patients During Chest Drainage Tube Removal After Cardiac Surgery: a Randomized Clinical Trial - Mohamad Mehdi Hatami; Khodayar Oshvandi; Mehdi Molavi Vardanajni; Yunes Mohamadi; Amir Shamas (Hamadan University of Medical Sciences, 2018)
Introduction: The removal of the chest tube drainage is a painful experience for patients. Painless pain and patient's discomfort is associated with reduced chest dilatation, respiratory dysfunction with hypoxemia, increased sympathetic response to myocardial ischemia, and increased general response to tachycardia. The purpose of this study was to investigate the use of cold compresses before removing the chest drainage tube on the comfort of patients after cardiac surgery. Method: This was a randomized clinical trial with 120 patients undergoing cardiac surgery in Farshchian Hospital in Hamadan in 1395. . The research units were randomly divided into three groups of interventional, placebo, and control groups of ICU patients undergoing cardiac surgery and had at least two duct drainage tubes. Cold compresses and placebo were placed around tubes for 20 minutes before removing the chest tubes. The patient's comfort level was measured using the visual analog scale (VAS) before, immediately after and 5 minutes after removal of the chest tube. Data analysis was done using SPSS16, Chi-square, and ANOVA. Results: There was no significant difference between demographic data in the studied groups. However, the average comfort score before, immediately after and 5 minutes after removing chest tube was significantly different in the groups (P =0.000). Conclusion: The results showed that the use of cold compresses around the chest tube before the removal of tubes in patients undergoing heart surgery increases the comfort of the patients.